1985
DOI: 10.1016/0014-5793(85)80314-8
|View full text |Cite
|
Sign up to set email alerts
|

Action of influenza virus neuraminidase on gangliosides

Abstract: The action of partly purified neuraminidase (NA) of influenza A virus, a mixture of detergent solubilized NA and haemagglutinin (HA) and of intact virions on gangliosides GTlb, GDla, GDlbr GM, was studied. The viral NA transformed GTlbmainly into GBlb with formation of only minor amounts of G,,. HA was found to inhibit the hydrolysis activity of viral NA. At the same time viral NA transformed Ga,,quantitatively into Ght, which was not hydrolyzed by the enzyme. These results suggest that the function of NA is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The substrate specificity of the various microbial sialidases varies, depending on the nature of substrate and the type of linkage between NANA and the neighbouring carbohydrate [1,15]. Thus, BACH & BRASHLER [5] have shown both similarities and differences in the action of various sialidases on rat mast cells.…”
Section: Discussionmentioning
confidence: 98%
“…The substrate specificity of the various microbial sialidases varies, depending on the nature of substrate and the type of linkage between NANA and the neighbouring carbohydrate [1,15]. Thus, BACH & BRASHLER [5] have shown both similarities and differences in the action of various sialidases on rat mast cells.…”
Section: Discussionmentioning
confidence: 98%
“…Quantitative determination of ganglioside components was carried out as in [21]. The ganglioside mixtures (10-20 nmol sialic acid) were separated by HPTLC as described above.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Our previous studies demonstrated that ganglioside GTl is involved in the reception of influenza virus and mediates entry of the virus into Ehrlich ascites carcinoma cells [4]. The virus was shown to convert G T l b mainly into ganglioside GDlb [5] the carbohydrate chain of which appears to be the minimal cell-surface structure capable of inducing influenza virus penetration into carcinoma cells. However, the mechanism by which gangliosides influence virus attachment and penetration remains obscure.…”
mentioning
confidence: 99%